Onlay foreskin flap anastomosed directly to the tunica albuginea: A short-term experimental study in rabbits. Issue 5 (October 2015) - Bacelar, H.; Rondon, A.V.; Mattos, R.; Quitzan, J.G.; Leslie, B.; Delcelo, R.; de Araújo, S.R.; Ortiz, V.; Macedo, A.
Summary: Introduction: In severe hypospadias, urethral plate division is necessary for curvature correction. To configure the new urethra, an approach has been described using a foreskin flap directly anastomosed in an 'onlay' fashion to the tunica albuginea of the corpora cavernosa. Results suggest that it is possible to use the corpus cavernosum albuginea as the posterior wall of the neourethra without the need of a dorsal graft. Objective: The present experimental study aimed to evaluate the histological characteristics and healing pattern of this procedure. Study design: Sixteen New Zealand male rabbits were divided into two groups of eight animals. Eight animals underwent 1-cm longitudinal dorsal incision of the penile urethra and the edges were anastomosed to the tunica albuginea (Group 1). Eight other animals underwent complete excision of 1.0 cm of penile urethra. Urethroplasty was performed using a foreskin flap directly anastomosed as an onlay to the albuginea, as shown in the figure (Group 2). Sacrifice and histological assessment was performed 2, 4, 8 and 12 weeks postoperatively. Results: In Group 1, a mild inflammatory process was noted that became almost imperceptible at 12 weeks. Fibrosis was mild at all stages in this group. Over time, a regenerative epithelium covered the corpus cavernosum. Immunohistochemistry using specific CK-7 and CK-20 confirmed the presence of urothelium. No complications were microscopically detected in this group. Group 2 presented with a more intense inflammatory infiltrate, which also resolved over time. Fibrosis was slightly more intense in this group, especially in animals that had urethral strictures. Group 2 presented with three fistulas, two were associated with urethral stricture. Histological evaluation showed the presence of epithelization over the albuginea, which turned out to be similar to the normal urothelium over time and was confirmed by immunohistochemistry. Non-keratinized stratified squamous epithelium of the foreskin flap showed good integration to the urethra. Discussion: Microscopic analysis showed that inflammation, fibrosis and complications were similar to previous studies. At 12 weeks there was a well-developed epithelium similar to normal urethra, which was confirmed by immunohistochemistry; this was similar to what occurs in the TIP technique, as previously demonstrated. It was hypothesized that the epithelium regeneration developed from the urethral edges, as demonstrated in other experimental studies. Conclusion: The albuginea was covered by mature urothelium after 12 weeks, which presumably grew from the urethral edges. The foreskin flap onlay that was directly anastomosed to the albuginea completely integrated and constituted the roof of the neourethra. Figure Procedure in Group 2. (A) Construction of 1.0-cm long urethral defect; (B) delimitation of foreskin flap on the ventral penile surface; (C) flap rotation from distal to proximal to cover the urethral defect; (D) flap sutured to the corpus cavernosum.